Alert prescribing of clozapine: a comparison of five drug-drug interaction sources - Jeroen Govaerts; Annelies Verluyten; Filip Bouckaert; Marc A. F. De Hert; Franciska A. M. Desplenter (SAGE Publishing, 2024)
Introduction: Clozapine, an antipsychotic used in the treatment of schizophrenia, is known for its serious side effects. In order to promote patient safety, drug-drug interaction (DDI) databases can be consulted by clinicians. In this study, the degree of consensus between five sources on DDIs with clozapine is determined. Methods: The summary of product characteristics of clozapine, Delphicare interaction database, Stockley's interaction checker, the Lexicomp interaction database, and the interaction database of Clinical Pharmacology are included. By comparing the original categories assigned to interactions with clozapine by the included DDI sources, a degree of consensus between sources is determined. Furthermore, based on the combined information, an evaluation on the severity of each potential interaction is made. Results: One hundred eighty-three potential DDIs with clozapine are retrieved from the five included sources. A consensus between sources is found in 47.5% ( n  = 87) of DDIs. Conclusion: This study shows major discrepancies between five different sources on DDIs with clozapine. The potential impact of the use of one specific database on patient safety and prescribing behavior could prove to be problematic.